2017
DOI: 10.1021/acsami.7b09891
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Graphene Sheets by Electrochemical Exfoliation of Graphite in Confined Space and Their Application in Transparent Conductive Films

Abstract: A novel electrochemical exfoliation mode was established to prepare graphene sheets efficiently with potential applications in transparent conductive films. The graphite electrode was coated with paraffin to keep the electrochemical exfoliation in confined space in the presence of concentrated sodium hydroxide as the electrolyte, yielding ∼100% low-defect (the D band to G band intensity ratio, I/I = 0.26) graphene sheets. Furthermore, ozone was first detected with ozone test strips, and the effect of ozone on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 70 publications
2
40
0
Order By: Relevance
“…This phenomenon is allegedly caused by the ability of Cu 2+ to work as a reducing agent in the reduction of oxygenated carbonaceous compounds under microwave irradiation. A similar result has been reported by Li et al in the process of graphene oxide reduction by metallic Cu [31]. Figure 2 (a) shows the x-ray diffractograms of raw graphite, EG, EG/Cu/Cu2O A, and EG/Cu/Cu2O B.…”
Section: C Photocatalytic Activity Measurementsupporting
confidence: 85%
“…This phenomenon is allegedly caused by the ability of Cu 2+ to work as a reducing agent in the reduction of oxygenated carbonaceous compounds under microwave irradiation. A similar result has been reported by Li et al in the process of graphene oxide reduction by metallic Cu [31]. Figure 2 (a) shows the x-ray diffractograms of raw graphite, EG, EG/Cu/Cu2O A, and EG/Cu/Cu2O B.…”
Section: C Photocatalytic Activity Measurementsupporting
confidence: 85%
“…Wang et al . demonstrated that paraffin coating outside the graphite electrode could effectively confine the electrochemical exfoliation to a defined volume 38 . However, intensive sonication in N-Methyl-2-pyrrolidone and further centrifugation were used as post-processing in this case.…”
Section: Prior Work In Electrochemical Exfoliationmentioning
confidence: 99%
“…Additional multi-steps are needed to reduce such functional graphene for supercapacitor applications. Electrochemical exfoliation, as a green method for preparing graphene sheets, owns unique advantages including easy operation, low cost, scalable production and controllable reaction conditions [12][13][14][15] . These traits enable electrochemical exfoliation a promising method to prepare high-quality and cost-effective graphene sheets for various applications.…”
Section: Introductionmentioning
confidence: 99%